Induction of systemic and mucosal immune response against Zika virus by vaccination with non-infectious chimeric VLPs - Luciana Agostina Fassola; Lucía Lara Rupil; Florencia Martínez; Guillermo Albrieu-Llinás; Marianela del Carmen Serradell (Scientific Reports)
Abstract The Zika virus (ZIKV) causes acute febrile illness and can lead to complications such as Guillain-Barré syndrome and congenital disorders. As arbovirus outbreaks increase, vaccination becomes a crucial preventive strategy. Currently, no commercial vaccines are available for ZIKV, which is transmitted by mosquitoes and bodily fluids, underscoring the need for a safe vaccine that induces both systemic and mucosal immune responses. In this study, we present a ZIKV vaccine candidate utilizing virus-like particles (VLPs) technology combined with variant-specific surface proteins (VSP) from Giardia lamblia. Previous research demonstrated that these VSP act as effective adjuvants and are resistant to gastrointestinal degradation, expanding administration possibilities via orogastric routes in addition to the conventional subcutaneous route. To develop the immunogen, we engineered retrovirus-derived VLPs decorated with the ZIKV envelope glycoprotein (ZIKV-E) as the target antigen, incorporating VSPs on their surface. Immunocompetent Balb/c mice were immunized with VSP-VLPs ZIKV-E via oral and subcutaneous routes. Immune characterization revealed robust systemic and mucosal humoral responses, as well as a specific cellular activation. Moreover, a significant neutralizing capacity of serum antibodies was observed. These findings highlight the potential of the vaccine candidate to elicit a targeted immune response, achieved through different administration methods.